Analysis of treatment adherence and cost among patients with epilepsy: a four‐year retrospective cohort study in Pakistan - Muhammad Arif Asghar; Ahad Abdul Rehman; Muhammad Liaquat Raza; Yousra Shafiq; Muhammad Asif Asghar (BMC, 2021)
Abstract Background The adherence pattern of antiepileptic drugs (AEDs) among patients with epilepsy is relatively lower in the United States and different European countries. However, adherence and cost analysis of AEDs in Asian countries have not been thoroughly studied. Therefore, the present study aimed to analyze the cost and adherence of AEDs and its associated factors in patients followed in Pakistan. Methods Data from prescriptions collected from patients with epilepsy who have visited the Outpatient Department (OPD) of different tertiary care hospitals at the cosmopolitan city of Karachi, Pakistan from December 2015 to November 2019. The mean follow-up period for each participant was about 22 months. Pairwise comparisons from Cox regression/hazard ratios were used to assess the predictors of adherence. Direct costs of AEDs were calculated and presented as the annual cost of drugs. Results A total of 11,490 patients were included in this study, 51.2 % were male and 48.8 % were female with a mean age of 45.2 ± 15.8 y. Levetiracetam was found as the most prescribing AED in all study participants (32.9 %). Of them, 49.1 % of patients continued their initial recommended treatment. However, 31.3 % of patients have discontinued the therapy, while, 19.6 % were switched to other AED. Adherence with initial treatment was more profound in male (57.4 %) patients, compared to female with a mean age of 44.2 years. Lamotrigine users (60.6 %) showed a higher tendency to retain on initially prescribed drugs. The total cost of epilepsy treatment in the entire study cohort was 153280.5 PKR ($941.9). By applying the Cox regression analysis, it can be observed that the patients with increasing age (OR, 2.04), migraine (OR, 2.21), psychiatric disorders (OR, 4.28), other comorbidities (OR, 1.52) and users of other than top five prescribing AEDs (2.35) were at higher risk of treatment discontinuation. However, levetiracetam (OR, 0.69), valproic acid (OR, 0.52), carbamazepine (OR, 0.81), lamotrigine (OR, 0.80) or lacosamide (OR, 0.65) users have more chances to continue their initial therapy. Conclusions Similar to western countries, the majority of patients with epilepsy exhibited low adherence with AEDs. Various associated factors for improving adherence were identified in this study.